Inventarisasi Khamir pada Ragi Tape yang Terbuat dari Tepung Beras (Oryza sativa L.) Varietas Lokal - Daniati, Eleutra; Kurniatuhadi, Rikhsan; Turnip, Masnur (JURNAL BIOLOGICA SAMUDRA, 2023)
White rice flour (Oryza sativa L.) is the main ingredient used by the Dayak community in the manufacture of tape yeast, the tape yeast is one of the substrates for the growth of microorganisms, one of which is yeast. Yeast belongs to the group of fungi that are unicellular in shape and have been isolated from various kinds of traditional fermented foods that are consumed such as tape. The purpose of this study was to determine the genus of yeast isolated from tape yeast made from white rice flour. This research was conducted in December 2021 – April 2022. Yeast isolates were identified based on macroscopic and microscopic observations of colonies from yeast cells, cell reproduction, and physiological tests with reference to the book The Yeast a Taxonomic Study. Based on the results of this study, 12 yeast isolates were obtained consisting of three genera, namely Kluyveromyces, Pichia and Saccharomyces.